2019
DOI: 10.1111/jocn.14935
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters and related factors in oesophageal cancer patients 3 months after surgery

Abstract: Aim To explore symptom clusters experienced by patients with oesophageal cancer 3 months after surgery and examine whether symptom clusters are related to demographic, clinical and quality of life variables. Background There are multiple symptoms in patients with oesophageal cancer after surgery, which seriously affect their quality of life. Exploring the mechanics of concurrent symptoms such as symptom clusters may facilitate the development of strategies to reduce the impact of these symptoms and improve qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
(68 reference statements)
4
19
0
Order By: Relevance
“…It might be because elderly patients had better coping strategies due to more life experience than that of young patients. Furthermore, in agree with previous studies, our data suggested that more female patients reported severe symptom distress of psycological SC than the male [7,21]. At last, the distress of psychological SC was in uenced by the patients' treatment outcome.…”
Section: Discussionsupporting
confidence: 92%
“…It might be because elderly patients had better coping strategies due to more life experience than that of young patients. Furthermore, in agree with previous studies, our data suggested that more female patients reported severe symptom distress of psycological SC than the male [7,21]. At last, the distress of psychological SC was in uenced by the patients' treatment outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Co-occurring and interrelated symptoms can be defined as symptom clusters [8,9], and those in one group are distinct from other SCs and have different symptoms [10,11]. Though some studies have explored the possibilities of SCs in esophageal cancer patients, the results were inconsistent [12,13]. Furthermore, SCs have a more significant effect on QoL due to synergistic action than each symptom alone [14].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery process for esophageal carcinoma patients post-surgery is complicated and lengthy owing to surgical trauma and reconstruction of the digestive tract [8]. At 3 months post-surgery, symptom burden, especially that of fatigue, appetite loss, re ux, and eating di culties, remains high [9]. Gastrointestinal symptoms such as re ux, eating di culties, diarrhoea, and appetite loss can persist 10 years postsurgery [8].…”
Section: Introductionmentioning
confidence: 99%